Pre-oxidized carbonized coconut shell-based closed-pore structure hard carbon negative electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611486312.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-23
- Publication Date
- 2026-10-30
AI Technical Summary
这一多步处理增加了工艺复杂度和化学试剂用量
(1)独创的“预碳化→空气预氧化→高温碳化”工艺路线。本发明以椰壳预碳化粉末(而非原始生物质)为预氧化对象,利用预碳化后碳骨架已初步成型的特点,使空气预氧化的造孔和官能团引入更为精准可控。这一“预碳化→预氧化→高温碳化”的路线中,预氧化后无需引入化学交联剂、活化剂或进行化学气相沉积处理即可直接高温碳化,实现了工艺的极简化,区别于现有技术中预氧化后需引入氯化铵交联(如CN121317693A),或需采用变温化学气相沉积(如CN121202125A)等复杂路线。
Smart Images

Figure CN123002824A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the technical field of sodium-ion battery anode materials, and relates to a pre-oxidized carbonized coconut shell-based closed-cell hard carbon anode material, its preparation method, and its application. Specifically, it relates to a hard carbon anode material obtained by using pre-carbonized coconut shell powder as a precursor and controlling the closed-cell structure and surface chemical properties through an air pre-oxidation process, its preparation method, and the application of this material in sodium-ion batteries. Background Technology
[0002] Sodium-ion batteries, with their advantages of abundant and widely distributed sodium resources and low cost, are considered an important supplement and alternative to lithium-ion batteries in the field of large-scale energy storage. Among sodium-ion battery anode materials, hard carbon materials, due to their large carbon interlayer spacing, abundant nanopores, and stable amorphous carbon structure, can provide effective sites for sodium ion insertion / extraction and pore-filling storage, and have become one of the most promising anode material systems for industrialization.
[0003] Coconut shells, a common agricultural waste, offer advantages such as abundant availability, renewability, low cost, and high carbon content, making them an ideal biomass precursor for preparing hard carbon anode materials. However, hard carbon materials prepared directly from coconut shells through simple carbonization often suffer from low reversible capacity and low initial coulombic efficiency (ICE). The core reason for these problems lies in the fact that traditional direct carbonization processes struggle to effectively control the microstructure of the precursor before carbonization, resulting in insufficient closed-pore content in the material after high-temperature carbonization—closed pores are key structural units for efficient sodium storage in the low-voltage plateau region through a "pore-filling" mechanism; simultaneously, the disorder and interlayer spacing of the carbon layers make it difficult to simultaneously meet the requirements of sodium storage capacity and rate performance.
[0004] To improve the structure and properties of hard carbon materials, various pretreatment strategies have been proposed in existing technologies: Regarding pre-oxidation, existing research has disclosed technical routes for using air pre-oxidation to introduce oxygen-containing functional groups and regulate the carbon microcrystalline structure of biomass raw materials. For example, CN121317704A discloses a method for preparing high-capacity sodium-ion battery anode hard carbon materials. This method involves introducing a crosslinking agent and catalyst for chemical crosslinking after air pre-oxidation, followed by low-temperature sintering and high-temperature sintering to prepare hard carbon materials. Although this method involves a pre-oxidation step, the purpose of pre-oxidation is to provide active sites for subsequent chemical crosslinking. The core process lies in the multi-step synergy of crosslinking and sintering, rather than pre-oxidation itself.
[0005] Regarding the hydrothermal / solvothermal pretreatment of biomass, CN121812537A discloses a method for preparing coconut shell-based hard carbon anode active materials. This method requires prepolymerizing and polymerizing coconut shell powder with phenolic and aldehyde monomers respectively to form a composite material, followed by pre-oxidation and carbonization. This method involves complex polymerization reactions, introduces additional organic reagents, and has a relatively cumbersome process route.
[0006] Regarding activated pore formation, CN121202125A discloses a method using coconut shells as raw material, activating the material with an activating agent to obtain porous carbon materials, and then performing variable-temperature chemical vapor deposition to construct closed-pore structures. This method requires the use of activating agents and chemical vapor deposition equipment, resulting in high process complexity and production costs.
[0007] Regarding the regulation of C=O functional groups, CN121591211A discloses a method for reconstructing C=O functional groups on the surface of coconut shell-based hard carbon materials. This method requires activation via a CO2 gas-solid reaction followed by heat treatment with citric acid mixed with the hard carbon material. This method involves modification after carbonization, has multiple process steps, and requires sophisticated equipment due to the gas-solid reaction.
[0008] Regarding cross-linking and pore-forming, CN121317693A discloses a method for preparing biomass-derived hard carbon anode materials, employing a process combining air oxidation and ammonium chloride-catalyzed dehydration and cross-linking. This method requires the additional introduction of ammonium chloride after air oxidation for catalytic cross-linking and low-temperature carbonization, utilizing the decomposition of ammonium chloride to form open nanopores, which are then closed at high temperatures to form closed pores. This multi-step process increases the complexity of the process and the amount of chemical reagents used.
[0009] In summary, the existing technology lacks a simple and efficient method for preparing hard carbon anode materials that can pre-construct abundant oxygen-containing functional groups and nanoporous structures in pre-carbonized biomass precursors by simply controlling the pre-oxidation temperature and pre-oxidation time without introducing additional chemical reagents, and then cause these pore structures to spontaneously close to form a large number of closed pores through subsequent high-temperature carbonization, thereby achieving high reversible capacity and high first coulombic efficiency. Summary of the Invention
[0010] To address the shortcomings and challenges of existing technologies, this invention provides a pre-oxidized carbonized coconut shell-based closed-cell hard carbon anode material, its preparation method, and its applications. This method features a simple process route that achieves the directional construction of the closed-cell structure without the need for additional chemical reagents. By combining air pre-oxidation with high-temperature carbonization in an inert atmosphere on pre-carbonized coconut shell powder, the pre-oxidation introduces a large number of oxygen-containing functional groups and nanopores in the precursor stage, driving the transformation of open pores into closed pores during subsequent high-temperature carbonization. This synergistically optimizes the closed-cell content, carbon interlayer spacing, degree of disorder, and C=O functional group distribution at the microstructural level, achieving high reversible capacity, high initial coulombic efficiency, and excellent rate performance.
[0011] To achieve the above objectives, the present invention provides a method for preparing a pre-oxidized carbonized coconut shell-based closed-cell hard carbon anode material, comprising the following steps: (S1) After crushing the coconut shell raw material, it is pre-carbonized under an inert atmosphere and then naturally cooled to obtain pre-carbonized coconut shell powder. (S2) The pre-carbonized coconut shell powder obtained in step (S1) is placed in an air atmosphere and heated to 350-550°C at a heating rate of 3-8°C / min, and held at that temperature for 0.5-2h for pre-oxidation. After natural cooling, a pre-oxidized precursor is obtained. The pre-oxidation utilizes air oxidation etching to construct oxygen-containing functional groups and nanoporous structures in the pre-carbonized coconut shell powder. The oxygen-containing functional groups include at least one of carboxyl, carbonyl, and hydroxyl groups, and the pore size of the nanoporous structures is less than 2nm. (S3) The pre-oxidized precursor obtained in step (S2) is heated to 1200-1600°C at a heating rate of 3-8°C / min under an inert atmosphere and held at that temperature for 1-4 hours for high-temperature carbonization. After natural cooling, it is ground into powder to obtain a coconut shell-based closed-pore hard carbon anode material. During the high-temperature carbonization process, the oxygen-containing functional groups constructed in step (S2) undergo thermal decomposition and release CO and / or CO2 gas. The release of the gas drives the pore walls of the nanopores to melt, shrink, and close, realizing the natural transformation from open pores to closed pores. At the same time, the carbon skeleton undergoes thermal condensation to form the interlayer spacing d. 002 The value is 3.82–4.00 Å and the disorder degree is I. D / I G It has a carbon microcrystalline structure of 1.6 to 1.8.
[0012] Further, in step (S1), the coconut shell raw material is washed, dried, and crushed to a particle size ≤1mm before pre-carbonization.
[0013] Further, in step (S1), the inert atmosphere is argon or nitrogen.
[0014] Furthermore, in step (S2), the pre-oxidation temperature is 450°C and the holding time is 1 hour.
[0015] Further, in step (S2), the oxygen content of the pre-oxidized precursor is 18.55 to 22.61 wt%, and the specific surface area BET is 10 to 25 times that of the pre-carbonized coconut shell powder.
[0016] Furthermore, in step (S3), the high-temperature carbonization temperature is 1400°C, and the holding time is 2 hours.
[0017] Further, in step (S3), the specific surface area (BET) of the obtained hard carbon anode material is 0.2% to 1.5% of that of the pre-oxidized precursor.
[0018] The second aspect of this invention provides a coconut shell-based closed-cell hard carbon anode material, which is prepared by the preparation method described in this invention.
[0019] Furthermore, the hard carbon anode material has at least one of the following characteristics: (1) Initial coulombic efficiency ≥ 89%, initial reversible charging capacity ≥ 370 mAh·g -1 (15 mA·g) -1 ); (2) Reversible capacity at a current density of 300 mA·g⁻¹ ≥ 290 mAh·g -1 .
[0020] A third aspect of the present invention provides a sodium-ion battery, comprising a negative electrode, wherein the negative electrode comprises the coconut shell-based closed-pore hard carbon negative electrode material described in the present invention.
[0021] Compared with existing inventions, the beneficial effects of the present invention are: (1) The original "pre-carbonization → air pre-oxidation → high-temperature carbonization" process route. This invention uses coconut shell pre-carbonized powder (rather than raw biomass) as the pre-oxidation object. Taking advantage of the fact that the carbon skeleton has been initially formed after pre-carbonization, the pore-forming and functional group introduction of air pre-oxidation are more precise and controllable. In this "pre-carbonization → pre-oxidation → high-temperature carbonization" route, there is no need to introduce chemical crosslinking agents, activators or chemical vapor deposition treatment after pre-oxidation before high-temperature carbonization can be carried out directly, which realizes the extreme simplification of the process. This is different from the complex routes in the prior art that require the introduction of ammonium chloride crosslinking after pre-oxidation (such as CN121317693A) or the use of variable temperature chemical vapor deposition (such as CN121202125A).
[0022] (2) Unique “pre-oxidation pore-forming → high-temperature pore-closing conversion” mechanism. This invention utilizes air pre-oxidation to pre-construct abundant oxygen-containing functional groups and nanopores in the precursor. During the high-temperature carbonization stage, the thermal decomposition of oxygen-containing functional groups drives the natural conversion of open pores to closed pores. This process does not rely on external activators for etching pore-forming or vapor deposition for pore blocking, but rather utilizes the intrinsic thermochemical evolution of the material to achieve the directional construction of closed-pore structures.
[0023] (3) Excellent comprehensive electrochemical performance. The prepared hard carbon anode material has an initial discharge capacity of 350 mAh·g. -1 Charging capacity reaches 390 mAh·g -1 The initial coulombic efficiency reached 91.9%; at 90 mA·g -1 After 100 cycles, the reversible capacity remains at 300 mAh·g -1 At 300, 600 and 900 mA·g -1The reversible capacities at high current densities were 306, 224, and 132 mAh·g, respectively. -1 It exhibits excellent cycle stability and rate performance.
[0024] (4) Significant advantages in green environmental protection and cost. Using agricultural waste coconut shells as raw materials, the pretreatment only uses air as the oxidation medium, without the need for alkaline activation, organic solvent soaking or expensive chemical reagents; the core equipment is only a tube furnace, with fewer process steps and strong parameter controllability, making it suitable for large-scale industrial production. Attached Figure Description
[0025] Figure 1 The X-ray diffraction (XRD) patterns of the hard carbon anode materials prepared in each embodiment and comparative example are shown. Figure 2 Raman spectra of the hard carbon anode materials prepared in each embodiment and comparative example; Figure 3 Nitrogen adsorption-desorption isotherms of the hard carbon anode materials prepared in each embodiment and comparative example; Figure 4 The first charge-discharge curves of the hard carbon anode materials prepared in each embodiment and comparative example are shown. Figure 5 The cycling performance diagrams are shown for the hard carbon anode materials prepared in each embodiment and comparative example. Figure 6 Rate performance diagrams of the hard carbon anode materials prepared in each embodiment and comparative example; Figure 7 The images show the electrochemical impedance spectroscopy (EIS) spectra of the hard carbon anode materials prepared in each embodiment and comparative example. Detailed Implementation
[0026] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0027] In one embodiment of the present invention, the technical solution is summarized as follows: A method for preparing a hard carbon anode material for sodium-ion batteries includes the following steps: (1) Pre-carbonization treatment: After washing and drying, the coconut shell raw material is crushed and pre-carbonized under an inert atmosphere. After cooling to room temperature, it is crushed and sieved to obtain pre-carbonized coconut shell powder. (2) Air pre-oxidation treatment: The pre-carbonized coconut shell powder obtained in step (1) is evenly spread out so that it is in full contact with air. It is heated to 300-600°C in an air atmosphere and kept at that temperature for 0.3-3 hours. After natural cooling, the pre-oxidized precursor is obtained.
[0028] (3) High-temperature carbonization treatment: The pre-oxidized precursor obtained in step (2) is subjected to high-temperature carbonization at 3-8°C·min under an inert atmosphere. -1 The temperature is increased to 1200-1600°C at a heating rate, held for 1-4 hours, and then naturally cooled to room temperature. The material is then ground into powder to obtain the pre-oxidized carbonized coconut shell-based closed-cell hard carbon anode material.
[0029] Preferably, the temperature of the air pre-oxidation treatment is 400-500°C, and the holding time is 0.5-2 hours.
[0030] More preferably, the temperature of the air pre-oxidation treatment is 450°C, and the holding time is 1 hour.
[0031] Preferably, the inert atmosphere is argon or nitrogen; the heating rate is 5°C·min. -1 The high-temperature carbonization temperature is 1400°C, and the holding time is 2 hours.
[0032] The core technical mechanism of the preparation method described in this invention lies in: a) Precursor pore formation and surface functionalization: Air pre-oxidation treatment introduces abundant oxygen-containing functional groups into the pre-carbonized coconut shell powder, and oxidative etching creates a large number of nanoscale pores in the carbon framework, significantly increasing the specific surface area of the precursor. The oxygen-containing functional groups and open pores formed in this stage lay a key foundation for the structural evolution during the subsequent high-temperature carbonization process.
[0033] b) Closed-pore transformation during high-temperature carbonization: In the subsequent high-temperature carbonization stage under an inert atmosphere, oxygen-containing functional groups undergo thermal decomposition and escape in the form of CO, CO2, etc. During this process, the open-pore nanopores formed in the pre-oxidation stage undergo structural rearrangement and contraction closure, and are largely transformed into closed-pore structures. At the same time, the carbon skeleton undergoes thermal condensation and rearrangement at high temperature, and some oxygen-containing functional groups are transformed into stable C=O functional groups. The resulting hard carbon material has comprehensive structural characteristics of low open-pore specific surface area, high closed-pore content, large carbon interlayer spacing, and high disorder.
[0034] c) Coordinated control of temperature and time: Pre-oxidation temperature and time are key process parameters that determine the above-mentioned structural evolution. If the temperature is too low or the time is too short, the amount of oxygen-containing functional groups introduced will be insufficient, the pore-forming effect will be limited, and the closed-pore conversion rate after carbonization will be low. If the temperature is too high (e.g., exceeding 550°C) or the time is too long (e.g., exceeding 2 hours), the precursor carbon skeleton will be excessively oxidized and ablated, which will lead to a significant increase in the open-pore specific surface area and the content of irreversible oxygen-containing functional groups in the carbonized material, thereby reducing the electrochemical performance.
[0035] In a second aspect, the present invention provides a hard carbon anode material for sodium-ion batteries prepared by the above-described preparation method.
[0036] A third aspect of the invention also provides the application of the hard carbon anode material in the anode of a sodium-ion battery, and a sodium-ion battery comprising the hard carbon anode material.
[0037] As a further preferred embodiment, the preparation process of the above-mentioned battery electrode negative electrode sheet includes the following steps: The sodium-ion battery hard carbon anode material, conductive agent, binder and water-to-alcohol solvent are mixed and coated on a metal current collector, and then vacuum dried to obtain the battery electrode anode sheet.
[0038] The technical solution of the present invention will now be clearly and completely described with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0039] Unless otherwise specified, the raw materials used in the following embodiments are all disclosed in the prior art, such as those that can be directly purchased or prepared according to the preparation methods disclosed in the prior art.
[0040] The coconut shells used in the following examples are commercially available food processing byproducts. Before use, they were washed with deionized water to remove surface impurities, dried at 80°C, and then sealed for storage. The argon and nitrogen gases had a purity ≥99.99%. The tube furnace was a high-temperature tube resistance furnace.
[0041] Example 1 A method for preparing a hard carbon anode material for sodium-ion batteries, specifically including the following steps: (1) Pre-carbonization treatment: The cleaned and dried coconut shells are crushed and pre-carbonized under an inert atmosphere to obtain pre-carbonized coconut shell powder (denoted as PC).
[0042] (2) Air pre-oxidation treatment: Weigh a certain amount of PC powder and spread it evenly in a corundum boat to ensure that the powder is in full contact with the air. Place the corundum boat in a tube furnace and heat it to 450°C in an air atmosphere for 1 hour. After natural cooling, the pre-oxidized precursor is obtained and is denoted as PC-450-1.
[0043] (3) High-temperature carbonization treatment: The PC-450-1 precursor obtained in step (2) is placed in a tube furnace and heated at 5°C·min under an argon atmosphere. -1 The temperature was increased to 1400°C at a rising rate and held for 2 hours. After the reaction was completed, the furnace was allowed to cool naturally to room temperature. The carbonized product was then removed and ground into powder to obtain the hard carbon anode material, denoted as HC-450-1.
[0044] Example 2 A method for preparing a hard carbon anode material for sodium-ion batteries, specifically including the following steps: (1) Pre-carbonization treatment: The cleaned and dried coconut shells are crushed and pre-carbonized under an inert atmosphere to obtain pre-carbonized coconut shell powder (denoted as PC).
[0045] (2) Air pre-oxidation treatment: Weigh a certain amount of PC powder and spread it evenly in a corundum boat to ensure that the powder is in full contact with the air. Place the corundum boat in a tube furnace and heat it to 350°C in an air atmosphere for 1 hour. After natural cooling, the pre-oxidized precursor is obtained and is denoted as PC-350-1.
[0046] (3) High-temperature carbonization treatment: The PC-350-1 precursor obtained in step (2) is placed in a tube furnace and heated at 5°C·min under an argon atmosphere. -1 The temperature was increased to 1400°C at a rising rate and held for 2 hours. After the reaction was completed, the furnace was allowed to cool naturally to room temperature. The carbonized product was then removed and ground into powder to obtain the hard carbon anode material, denoted as HC-350-1.
[0047] Example 3 A method for preparing a hard carbon anode material for sodium-ion batteries, specifically including the following steps: (1) Pre-carbonization treatment: The cleaned and dried coconut shells are crushed and pre-carbonized under an inert atmosphere to obtain pre-carbonized coconut shell powder (denoted as PC).
[0048] (2) Air pre-oxidation treatment: Weigh a certain amount of PC powder and spread it evenly in a corundum boat to ensure that the powder is in full contact with the air. Place the corundum boat in a tube furnace and heat it to 550°C in an air atmosphere, and hold it for 1 hour. After natural cooling, the pre-oxidized precursor is obtained, which is denoted as PC-550-1.
[0049] (3) High-temperature carbonization treatment: The PC-550-1 precursor obtained in step (2) is placed in a tube furnace and heated at 5°C·min under an argon atmosphere. -1 The temperature was increased to 1400°C at a rising rate and held for 2 hours. After the reaction was completed, the furnace was allowed to cool naturally to room temperature. The carbonized product was then removed and ground into powder to obtain the hard carbon anode material, denoted as HC-550-1.
[0050] Example 4 A method for preparing a hard carbon anode material for sodium-ion batteries, specifically including the following steps: (1) Pre-carbonization treatment: The cleaned and dried coconut shells are crushed and pre-carbonized under an inert atmosphere to obtain pre-carbonized coconut shell powder (denoted as PC).
[0051] (2) Air pre-oxidation treatment: Weigh a certain amount of PC powder and spread it evenly in a corundum boat to ensure that the powder is in full contact with the air. Place the corundum boat in a tube furnace and heat it to 450°C in an air atmosphere, and hold it for 0.5 hours. After natural cooling, the pre-oxidized precursor is obtained, denoted as PC-450-0.5.
[0052] (3) High-temperature carbonization treatment: The PC-450-0.5 precursor obtained in step (2) is placed in a tube furnace and heated at 5°C·min under an argon atmosphere. -1 The temperature was increased to 1400°C at a rising rate and held for 2 hours. After the reaction was completed, the furnace was allowed to cool naturally to room temperature. The carbonized product was then removed and ground into powder to obtain the hard carbon anode material, denoted as HC-450-0.5.
[0053] Example 5 A method for preparing a hard carbon anode material for sodium-ion batteries, specifically including the following steps: (1) Pre-carbonization treatment: The cleaned and dried coconut shells are crushed and pre-carbonized under an inert atmosphere to obtain pre-carbonized coconut shell powder (denoted as PC).
[0054] (2) Air pre-oxidation treatment: Weigh a certain amount of PC powder and spread it evenly in a corundum boat to ensure that the powder is in full contact with the air. Place the corundum boat in a tube furnace and heat it to 450°C in an air atmosphere for 2 hours. After natural cooling, the pre-oxidized precursor is obtained, which is denoted as PC-450-2.
[0055] (3) High-temperature carbonization treatment: The PC-450-2 precursor obtained in step (2) is placed in a tube furnace and heated at 5°C·min under an argon atmosphere. -1 The temperature was increased to 1400°C at a rising rate and held for 2 hours. After the reaction was completed, the furnace was allowed to cool naturally to room temperature. The carbonized product was then removed and ground into powder to obtain the hard carbon anode material, denoted as HC-450-2.
[0056] Comparative Example 1 This comparative example provides a method for preparing hard carbon anode materials by direct high-temperature carbonization without air pre-oxidation treatment. The specific steps are as follows: (1) Pre-carbonization treatment: The cleaned and dried coconut shells are crushed and pre-carbonized under an inert atmosphere to obtain pre-carbonized coconut shell powder (denoted as PC).
[0057] (2) High-temperature carbonization treatment: A certain amount of PC powder is placed directly into a tube furnace and heated at 5°C·min under an argon atmosphere. -1 The temperature was increased to 1400°C at a certain heating rate and held for 2 hours. After natural cooling, it was ground into powder to obtain a hard carbon anode material, denoted as HC.
[0058] Structural and compositional characterization The precursors and final products prepared in the above embodiments and comparative examples were systematically characterized in terms of structure and composition.
[0059] (I) Specific surface area analysis of precursors The specific surface area of each precursor was characterized using nitrogen adsorption-desorption. The results showed that the specific surface area of the untreated PC precursor was 30.4 m². 2 ·g -1 After pre-oxidation in air at 450°C for 1 hour, the specific surface area of PC-450-1 significantly increased to 536.6 m². 2 ·g -1 After further carbonization at 1400°C, the specific surface area of HC-450-1 decreased sharply to 3.0 m². 2 ·g -1 .
[0060] The above results indicate that air pre-oxidation treatment creates a large number of nanoscale open pores in the carbon skeleton of pre-carbonized coconut shell powder through oxidative etching. During the subsequent high-temperature carbonization process, these open pores undergo a closure transformation, which significantly reduces the open pore specific surface area of the final hard carbon material and forms a rich closed pore structure.
[0061] (II) Characterization of graphite microcrystalline structure X-ray diffraction (XRD) was used to characterize the various hard carbon materials. For example... Figure 1 As shown, the microcrystalline structure parameters calculated from the XRD patterns are summarized in Table 1.
[0062] Table 1. Graphite microcrystalline structure parameters of various hard carbon anode materials As shown in Table 1, with the increase of pre-oxidation temperature and time, the d of the obtained hard carbon material increases. 002The increasing interlayer spacing and decreasing graphite crystallite sizes La and Lc indicate that the graphitization degree of the material is effectively suppressed, while the disorder increases. This structural evolution is attributed to the oxygen-containing functional groups introduced during the pre-oxidation process hindering the regular arrangement and ordered stacking of carbon layers during high-temperature carbonization, thus forming a more disordered carbon microcrystalline structure. The increased interlayer spacing helps to lower the energy barrier for sodium ion diffusion between carbon layers, and the disordered carbon microcrystalline structure provides more active sites for sodium storage.
[0063] (III) Raman spectroscopy characterization Raman spectroscopy was used to characterize various hard carbon materials. For example... Figure 2 As shown, approximately 1350 cm⁻¹ in the Raman spectrum -1 The D peak at approximately 1590 cm -1 The intensity ratio of the G peak at (I) D / I G Ic is an important indicator for measuring the degree of disorder in carbon materials. Results show that with increasing pre-oxidation temperature, Ic... D / I G The ratio continues to increase, with HC-550-1 having the highest I. D / I G The value indicates that moderate pre-oxidation treatment can effectively increase the disorder of carbon materials and form more abundant defect sites.
[0064] (iv) Characterization of pore structure like Figure 3 As shown, the pore structure of each hard carbon material was characterized by nitrogen adsorption-desorption method, and the results are summarized in Table 2.
[0065] Table 3 Specific surface area of various hard carbon materials As shown in Table 2, HC-450-1 has the lowest BET specific surface area (3.0 m²). 2 ·g -1 ), only for directly carbonized sample HC (8.2 m 2 ·g -1 The open-pore specific surface area is 36.6%. The extremely low open-pore specific surface area effectively reduces the contact area between the electrode material and the electrolyte, suppressing interfacial side reactions and irreversible capacity loss, thus improving the initial coulombic efficiency. Based on the above precursor specific surface area data, it can be inferred that although PC-450-1 has an extremely high open-pore specific surface area after pre-oxidation, a large number of open pores close after high-temperature carbonization, transforming into a closed-pore structure favorable for sodium storage.
[0066] However, when the pre-oxidation temperature is increased to 550°C, due to excessive oxidation and ablation of the precursor carbon skeleton, effective pore closure cannot be achieved after carbonization, resulting in a significant increase in the specific surface area of HC-550-1 to 12.5 m².2 ·g -1 This will increase irreversible side reactions between the electrode and the electrolyte, reducing coulombic efficiency.
[0067] Electrochemical performance testing Coin cell assembly: The hard carbon anode material, conductive carbon black (Super P), and polyvinylidene fluoride (PVDF) prepared in each embodiment and comparative example were mixed evenly at a mass ratio of 8:1:1. An appropriate amount of N-methylpyrrolidone (NMP) was added to grind and prepare a slurry, which was then evenly coated onto a copper foil current collector and vacuum dried at 100°C for 12 hours. Circular electrode sheets with a diameter of 12 mm were cut as working electrodes, sodium metal sheets were used as counter and reference electrodes, glass fiber membrane (Whatman GF / D) was used as the separator, and a 1M NaPF6 solution of ethylene carbonate / dimethyl carbonate (EC / DMC volume ratio 1:1) was used as the electrolyte. CR2025 coin cells were assembled in an argon-filled glove box.
[0068] Electrochemical testing conditions: Constant current charge-discharge test voltage range is 0.01~2.0V (vs Na / Na) + ).like Figure 4 As shown, at 15 mA·g -1 The initial charge-discharge capacity and initial coulombic efficiency were tested at current density, and the results are summarized in Table 3. (At 90 mA·g) -1 Cyclic performance was tested at (0.3C). Rate performance was tested at 30, 90, 300, 600, and 900 mA·g. -1 The electrochemical impedance spectroscopy (EIS) was performed at a current density of 100 kHz to 0.01 Hz, with an AC perturbation amplitude of 5 mV.
[0069] (a) Initial charge and discharge performance Table 3. Initial charge-discharge performance of various hard carbon anode materials (15 mA·g) -1 ) As shown in Table 3, HC-450-1 exhibits the best initial charge-discharge performance: the initial discharge capacity is 390 mAh·g. -1 The charging capacity is 358 mAh·g -1 The initial coulomb efficiency reached 91.9%.
[0070] The excellent initial coulombic efficiency of HC-450-1 is mainly attributed to: its extremely low open-pore specific surface area (3.0 m²). 2 ·g -1It effectively inhibits the irreversible decomposition of electrolyte on the electrode surface and the excessive growth of SEI film; the abundant C=O functional groups reduce irreversible capacity loss through reversible Faraday reactions; the abundant closed-pore structure is conducive to the efficient and reversible storage of sodium ions.
[0071] When the pre-oxidation temperature was increased to 550°C or the time was extended to 2 h, although the reversible capacity was still better than that of HC, the electrochemical performance decreased due to the increase in open pore surface area and irreversible oxygen-containing functional groups caused by excessive pre-oxidation. This indicates that precise control of the pre-oxidation process parameters is crucial to achieving optimal performance.
[0072] (ii) Cyclic performance like Figure 5 As shown, each hard carbon anode material at 90 mA·g -1 Cycling performance tests at current density showed that after 100 cycles, the reversible capacity of HC-450-1 remained at 300 mAh·g. -1 It exhibits excellent capacity retention and demonstrates superb cycle stability.
[0073] (III) Ratio Performance like Figure 6 As shown, the rate performance test results of various hard carbon anode materials are as follows: HC-450-1 achieves rate performance at 300, 600, and 900 mA·g -1 The reversible capacities at high current densities were 306, 224, and 132 mAh·g, respectively. -1 It exhibits excellent rate performance. This significant improvement in rate performance is attributed to: increased carbon interlayer spacing (d... 002 =3.88 nm) effectively reduced the diffusion barrier of sodium ions between carbon layers; abundant defects and nanopores provided a fast transport channel for sodium ions; the Faraday pseudocapacitance provided by the C=O functional group improved the material's response speed under high current.
[0074] (iv) Electrochemical impedance spectroscopy analysis like Figure 7 As shown, the electrochemical impedance spectroscopy (EIS) analysis results of various hard carbon anode materials indicate that HC-450-1 has the smallest interfacial charge transfer impedance and the largest sodium ion diffusion coefficient. The smaller interfacial charge transfer impedance indicates that the HC-450-1 electrode / electrolyte interface has excellent charge transfer kinetics; the larger sodium ion diffusion coefficient indicates that the unique closed-pore structure and expanded carbon interlayer spacing of HC-450-1 are conducive to rapid bulk diffusion of sodium ions, which is the electrochemical essence of its excellent rate performance.
[0075] Mechanism analysis The technical mechanism of this invention is analyzed and explained below based on characterization results and electrochemical test data. These analyses should not be construed as limiting the scope of protection of this invention.
[0076] In this invention, the air pre-oxidation step is the core key to achieving the technical effect. The precise selection of the pre-oxidation temperature directly determines the degree of pore formation and the amount of oxygen-containing functional groups introduced into the precursor, thereby affecting the proportion of closed-cell structures and electrochemical performance of the material after high-temperature carbonization.
[0077] Specifically, during the air pre-oxidation stage, the pre-carbonized coconut shell powder undergoes an oxidation reaction in an oxygen-containing atmosphere. The surface of the carbon skeleton is partially oxidized and etched to form nanoscale openings, while simultaneously generating a large number of oxygen-containing functional groups such as CO, C=O, and OC=O. When the pre-oxidation temperature is 450°C, it can effectively create pores in the carbon skeleton, introduce sufficient oxygen-containing functional groups, and avoid excessive ablation and damage to the carbon skeleton.
[0078] In the subsequent high-temperature carbonization stage (1400°C, inert atmosphere), oxygen-containing functional groups undergo thermal decomposition, releasing gases such as CO and CO2. The carbon skeleton undergoes intense thermal condensation and structural rearrangement. During this process, the nanopores formed in the pre-oxidation stage shrink and close under high temperature, largely transforming into closed-pore structures. These closed pores provide a sealed nanoscale storage space for sodium ions, enabling efficient sodium storage in the low-voltage plateau region through a "pore-filling" mechanism. This is the core structural basis for the high reversible capacity of HC-450-1. Simultaneously, due to the extensive closure of the pores, the specific surface area of the material's pores is significantly reduced, effectively suppressing irreversible side reactions between the electrode and the electrolyte, thus significantly improving the initial coulombic efficiency.
[0079] When the pre-oxidation temperature is too low (350°C), the oxidation reaction is insufficient, the introduction of oxygen-containing functional groups and nanopores in the precursor is limited, the pore-closing conversion rate after carbonization is low, and the performance improvement is limited. When the pre-oxidation temperature is too high (550°C) or the time is too long (2 hours), the carbon skeleton has already undergone excessive ablation in the pre-oxidation stage, and some carbon skeleton structures are irreversibly destroyed. After carbonization, the open pores cannot be effectively closed, resulting in an increase in specific surface area and an increase in irreversible oxygen-containing functional groups, which in turn reduces the material's initial coulombic efficiency and cycle stability.
[0080] Furthermore, the C=O groups in the oxygen-containing functional groups can undergo reversible redox reactions during charge and discharge, contributing additional Faraday pseudocapacitance. The increased carbon interlayer spacing and decreased graphite crystallite size facilitate rapid diffusion and insertion / extraction of sodium ions. The synergistic optimization of the closed-pore structure, C=O functional groups, and carbon layer structure endows the HC-450-1 material with excellent high-rate performance and cycling stability.
[0081] The embodiments of this application have been described above with reference to the accompanying drawings. Specific examples have been used to illustrate the principles and implementation methods of this application. The description of the above embodiments is only for the purpose of helping to understand the core ideas of this application. However, this application is not limited to the specific embodiments described above. The specific embodiments described above are merely illustrative and not restrictive. Those skilled in the art can make many other forms under the guidance of this application without departing from the spirit and scope of the claims, and all of these forms are within the protection scope of this application.
Claims
1. A method for preparing a pre-oxidized carbonized coconut shell-based closed-cell hard carbon anode material, characterized in that, Includes the following steps: (S1) After crushing the coconut shell raw material, it is pre-carbonized under an inert atmosphere and then naturally cooled to obtain pre-carbonized coconut shell powder. (S2) The pre-carbonized coconut shell powder obtained in step (S1) is placed in an air atmosphere and heated to 350-550°C at a heating rate of 3-8°C / min, and held at that temperature for 0.5-2h for pre-oxidation. After natural cooling, a pre-oxidized precursor is obtained. The pre-oxidation utilizes air oxidation etching to construct oxygen-containing functional groups and nanoporous structures in the pre-carbonized coconut shell powder. The oxygen-containing functional groups include at least one of carboxyl, carbonyl, and hydroxyl groups. (S3) The pre-oxidized precursor obtained in step (S2) is heated to 1200-1600°C at a heating rate of 3-8°C / min under an inert atmosphere and held at that temperature for 1-4 hours for high-temperature carbonization. After natural cooling, it is ground into powder to obtain a coconut shell-based closed-pore hard carbon anode material. During the high-temperature carbonization process, the oxygen-containing functional groups constructed in step (S2) undergo thermal decomposition and release CO and / or CO2 gas. The release of the gas drives the pore walls of the nanopores to melt, shrink, and close, realizing the natural transformation from open pores to closed pores. At the same time, the carbon skeleton undergoes thermal condensation to form the interlayer spacing d. 002 The value is 3.82–4.00 Å and the disorder degree is I. D / I G It has a carbon microcrystalline structure of 1.6 to 1.
8.
2. The preparation method according to claim 1, characterized in that, In step (S1), the coconut shell raw material is washed, dried, and crushed to a particle size ≤1mm before pre-carbonization.
3. The preparation method according to claim 1, characterized in that, In step (S1), the inert atmosphere is argon or nitrogen.
4. The preparation method according to claim 1, characterized in that, In step (S2), the pre-oxidation temperature is 450°C and the holding time is 1 hour.
5. The preparation method according to claim 1, characterized in that, In step (S2), the specific surface area (BET) of the pre-oxidized precursor is 10 to 25 times that of the pre-carbonized coconut shell powder.
6. The preparation method according to claim 1, characterized in that, In step (S3), the high-temperature carbonization temperature is 1400°C and the holding time is 2 hours.
7. The preparation method according to claim 1, characterized in that, In step (S3), the specific surface area (BET) of the obtained hard carbon anode material is 0.2% to 1.5% of that of the pre-oxidized precursor.
8. A coconut shell-based closed-cell hard carbon anode material, characterized in that, It is prepared by the preparation method according to any one of claims 1-7.
9. The hard carbon anode material according to claim 8, characterized in that, The hard carbon anode material has at least one of the following characteristics: (1) Initial coulombic efficiency ≥ 89%, initial reversible charging capacity ≥ 370 mAh·g -1 (15 mA·g) -1 ); (2) Reversible capacity at a current density of 300 mA·g⁻¹ ≥ 290 mAh·g -1 .
10. A sodium-ion battery, comprising a negative electrode, characterized in that, The negative electrode comprises the coconut shell-based closed-cell hard carbon negative electrode material as described in claim 8 or 9.
Citation Information
Patent Citations
Method for preparing hard carbon negative electrode material, hard carbon negative electrode material and sodium ion battery
CN121202125A
Sodium-ion battery biomass derived hard carbon negative electrode material and preparation method and application thereof based on cross-linking pore-forming
CN121317693A
High-capacity sodium ion battery negative electrode hard carbon material and preparation method thereof
CN121317704A
